الحِجاَجُ و آليَاته(اللّغويّة) في الدّرْس اللّغويّ العَربيّ وآيات الذّكرِ الحَكِيم - كرباع, علي (University of El-oued, 2020)
الملخص يتناول المقال أحَد آليّات الحجاج ألا وهي الآليات اللّغويّة في الدّرس اللّغويّ عنْد العرب و مُختلف اسْتعمالاتها في الخطاب القرآنيّ , و ما يصوغ حجاجيّته علاوة على قدسيّته ؛كوْنه خطابًا,والخطاب يقْتضي التّأثير والإقناع على حدّ قوْل بنيفسيتْ:"الخِطاب في أعمّ مفاهيمه كلّ قوْل يفترض متكلّما وسامعا, مع توفّر , مقْصد التّأثير "على أراء المتلقّي وسلوكاته , واسْتمالة النّفوس وتوْجيه العقول , لذا وظّف الكثير من الرّوابط الحجاجيّة التي تُؤمِّن هذه الغايات,لذا ما مدى توظيفه للآليات خاصّة اللّغويّة وما الغرض من اسْتعْمالاتها؟. Abstract: This article deals with the mechanisms of the Argumentation, namely the linguistic mechanisms, in the Arabic linguistic lesson, and its different uses in the Quranic discourse, and what formulates his Argumentation?, Furthermore on his sacredness as a discourse, and the discourse requires influence and persuasion, According to Benifset: “The discours in its most general concepts, Every statement supposed a speaker and a listener, With availability of Intent on the recipient Opinions and its behavior, And the induce of souls, and guidance of minds, So he made a lot of Argumentative connections, That secure these Goals, So how much is his use of these mechanisms Especially the linguistic one? and What is the purpose of its uses?.
مقال. Ex Professo. مج5. ع.1. جامعة الوادي
Keywords: الكلمات المفتاحية: الحجاج , اآلليات اللغوية , اللدرس اللغوي , الخطاب القرآني , اإلقناع; Key word; Argumentation- linguistic mechanisms- linguistic lesson- Quranic discourse- Persuasion.